Molecular and Serological Evaluation of Neospora caninum Infec-tion in Dogs from a Rural Setting in Fars Province, Southern Iran - Morvarid HARIRI (Iranian Journal of Parasitology, 2021)
Background: Dogs, as the definitive host of Neospora caninum, are important in the epidemiology of this parasitic infection. We aimed to determine the prevalence of N. caninum infection in a dog population from a rural setting in Fars Province, Southern Iran, using a combination of molecular and serological techniques.